2022
DOI: 10.1515/nanoph-2022-0141
|View full text |Cite
|
Sign up to set email alerts
|

Polymer modulators in silicon photonics: review and projections

Abstract: Optical modulators are vital for many applications, including telecommunication, data communication, optical computing, and microwave photonic links. A compact modulator with low voltage drive requirement, low power, high speed, and compatibility with CMOS foundry process is highly desirable. Current modulator technologies in Si suffer from trade-offs that constrain their power, performance (speed, drive voltage), and area. The introduction of additional materials to the silicon platform for efficient phase sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 112 publications
0
15
0
Order By: Relevance
“…Yet, very recently it was shown that crystalline BaTiO 3 thin films can be grown on both silicon as well as low index isolating substrates. , Such platforms are extremely promising for EO applications since they demonstrated extremely large Pockels coefficients, with r 33 values up to 340 pm/V, that is, one order of magnitude higher than in LiNbO 3 . The challenges of top-down nanofabrication listed in detail in Section , along with the advancements in bottom-up nanofabrication, fostered the investigation of metasurfaces composed of BaTiO 3 nanoparticle films for EO applications. , However, sizable drops in the values of the Pockels coefficient as well as the χ (2) have been reported for nanoparticles of small size (e.g., r 33 ∼ 37 pm/V for 50 nm nanoparticle diameter). , Other materials, like organic polymers, can also show large EO coefficients . Recently, EO silicon metasurfaces were realized by infiltrating them with JRD1:PMMA that exhibits r 33 ∼ 100 pm/V .…”
Section: Linbo3 Metasurfaces For Nonlinear Quantum and Electro-opticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, very recently it was shown that crystalline BaTiO 3 thin films can be grown on both silicon as well as low index isolating substrates. , Such platforms are extremely promising for EO applications since they demonstrated extremely large Pockels coefficients, with r 33 values up to 340 pm/V, that is, one order of magnitude higher than in LiNbO 3 . The challenges of top-down nanofabrication listed in detail in Section , along with the advancements in bottom-up nanofabrication, fostered the investigation of metasurfaces composed of BaTiO 3 nanoparticle films for EO applications. , However, sizable drops in the values of the Pockels coefficient as well as the χ (2) have been reported for nanoparticles of small size (e.g., r 33 ∼ 37 pm/V for 50 nm nanoparticle diameter). , Other materials, like organic polymers, can also show large EO coefficients . Recently, EO silicon metasurfaces were realized by infiltrating them with JRD1:PMMA that exhibits r 33 ∼ 100 pm/V .…”
Section: Linbo3 Metasurfaces For Nonlinear Quantum and Electro-opticsmentioning
confidence: 99%
“…84,85 Other materials, like organic polymers, can also show large EO coefficients. 186 Recently, EO silicon metasurfaces were realized by infiltrating them with JRD1:PMMA that exhibits r 33 ∼ 100 pm/V. 187 Despite such large Pockels coefficients, organic polymers are typically affected by temperature and chemical instabilities.…”
Section: Electro-optical Modulation With Ultrathin Opticalmentioning
confidence: 99%
“…[5,6] Poled polymers show an impressive modulation efficiency with an order of magnitude larger electro-optic coefficient compared to lithium niobate, but the material stability is hindering its use in long-term applications. [7,8] Plasmonic structures permit the highest electric field confinement but they are subject to high optical losses and low damage threshold. [9] Non-centrosymmetric metal-oxides, first only available as bulk crystals, show rather large second-order susceptibility coefficients, high damage threshold, and a wide transparency range.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6 ] Poled polymers show an impressive modulation efficiency with an order of magnitude larger electro‐optic coefficient compared to lithium niobate, but the material stability is hindering its use in long‐term applications. [ 7,8 ] Plasmonic structures permit the highest electric field confinement but they are subject to high optical losses and low damage threshold. [ 9 ]…”
Section: Introductionmentioning
confidence: 99%
“…Electro‐optic (EO) modulator is the key component for optical communication system, which could provide high‐quality phase modulation with tremendous speed. [ 2,4‐5 ] State‐of‐the‐art silicon photonics have been demonstrated as the suitable platform for dense integration of complex photonic devices by using mature technology and process toolsets from semiconductor manufacture process. [ 6‐7 ] Due to the lack of intrinsic second‐order non‐linearity, however, silicon photonics rely on the plasma dispersion effect that derives from carrier injection by application of a voltage.…”
Section: Introductionmentioning
confidence: 99%